Pengaruh Kompetensi Guru, Pola Asuh Orang Tua dan Lingkungan Belajar terhadap Motivasi Belajar Siswa MA NW Kotaraja Lombok Timur NTB - Musyaibin Musyaibin; Muhammad Yusron Maulana El-Yunusi; Didit Darmawan (Journal on Education, 2024)
Motivation and learning have a mutually influencing relationship in the educational context. Teacher competence and parenting patterns emerge as key factors that can influence students' learning motivation, which ultimately affects the quality of their learning outcomes. This quantitative research aims to analyze the direct impact of teacher competence and parenting patterns on student learning motivation at MA NW Kotaraja, East Lombok, NTB. Through the use of questionnaires as data collection instruments and multiple linear regression analysis, the research results show that teachers' understanding of subject matter and their ability to convey it effectively has a positive impact on student learning motivation. Furthermore, supportive parenting styles, providing emotional support, and providing positive encouragement also have a significant influence on students' learning motivation. These results highlight the important role of teachers and parents in forming a motivating learning environment, which in turn can improve the quality of learning and student learning outcomes at MA NW Kotaraja.